Conservation Practices in Tobacco Production Increase Large Aggregates and Associated Carbon and Nitrogen. Issue 6 (11th December 2015) - Zou, Congming; Pearce, Robert C.; Grove, John H.; Coyne, Mark S.
Abstract : Burley tobacco ( Nicotiana tobacum L. ) production in Kentucky is typically tillage intensive and is often mono‐cropped. Intensive tillage has been reported to degrade soil structure and deplete soil organic carbon (SOC) and total soil nitrogen (TSN) stocks. This study assessed the effect of tillage, crop rotation, and N fertilizer application on soil structure, water‐stable aggregation, and aggregate‐associated SOC and TSN concentrations and stocks for rotations including burley tobacco. Four burley tobacco production systems (main plots) were established in 2007 on a Bluegrass‐Maury (fine, mixed, active, mesic Typic Paleudalf) silt loam soil including: (i) no‐tillage continuous tobacco (NT‐Tobacco); (ii) conventional tillage continuous tobacco (CT‐Tobacco); (iii) 2‐yr sod ( Festuca arundinacea Schreb.) 1‐yr no‐tillage tobacco (NT‐Rotation); (iv) 2‐yr sod and 1‐yr conventional tillage tobacco (CT‐Rotation). In 2012, two N rates (0 and 280 kg N ha ‐1 ) were applied to split plots. Soil samples were taken in Spring 2013 to determine water‐stable aggregate‐size distributions and associated SOC and TSN concentrations and stocks. Compared with conventional tillage and tobacco monoculture, no‐tillage and rotation with sod significantly increased macroaggregate fractions (>250 μm), and associated SOC and TSN stocks at the expense of the silt‐clay size class (<53 μm) and associated SOC and TSN stocks. Although previous fertilizer N application had no significant effect on whole‐soil SOC and TSN stocks, a significant interaction with crop rotation on macroaggregate distribution and macroaggregate‐associated SOC and TSN stocks was observed. Using NT and/or rotation practices in burley tobacco production maintains desirable soil physical and chemical properties via macroaggregate stabilization, which leads to the conservation of SOC and TSN stocks.